The Impact of Alfamart Employee Recruitment Flyer Design on Job Application Interest - Miftahul Khairah Jumhur; Suparni Sampetan; Sukri Sukri (MANAZHIM, 2026)
The increasingly intense competition in the labor market requires companies to present recruitment media capable of attracting prospective applicants’ interest, one of which is through flyer design. However, studies on the influence of flyer design on the intention to apply for jobs remain limited, particularly those that combine respondents’ subjective assessments with objective visual analysis. This study aimed to examine the influence of Alfamart employee recruitment flyer design on the intention to apply for jobs among prospective applicants aged 18–30 years in Palopo City. This quantitative study employed a pretest–posttest design with 30 respondents. Data were collected through questionnaires and visual analysis using a MATLAB-based Convolutional Neural Network (CNN) to objectively assess flyer design quality. The variables examined included color, typography, layout, clarity of information, and the alignment of the design with the company’s image, while the data were analyzed using a paired-sample t-test and linear regression. The results showed that respondents held positive perceptions of the Alfamart recruitment flyer, particularly in terms of information clarity and the professional impression of the company, and the paired-sample t-test indicated no significant increase in the intention to apply for jobs after viewing the flyer (p > 0.05). However, the regression results indicated a significant effect of flyer design quality on the intention to apply, with an R² value of 0.959, meaning that 95.9% of the variance in the intention to apply was explained by flyer design quality. The CNN analysis also showed that clarity of information and simplicity of design were dominant factors compared with purely technical visual aspects. In conclusion, flyer design quality has a significant influence on the intention to apply when it is evaluated personally by prospective applicants, and the implications of this study underscore the importance of designing recruitment flyers that are informative, simple, and aligned with the characteristics of young people to enhance the effectiveness of the recruitment process.